NMR Spectroscopic Characterization of Flame‐Made Amorphous Silica‐Alumina for Cyclohexanol and Glyceraldehyde Conversion. Issue 1 (3rd December 2019) - Wang, Zichun; Jiang, Yijiao; Stampfl, Catherine; Baiker, Alfons; Hunger, Michael; Huang, Jun
Abstract: Amorphous silica‐aluminas (ASAs), possessing both Brønsted acid sites (BAS) and Lewis acid sites (LAS), are important bifunctional catalysts in various industrial applications. Solid‐state NMR spectroscopy has been widely used for characterizing the local structure and the surface sites of ASAs with probe molecules. In this work, four‐, five‐ and six‐coordinated Al species have been observed on the flame‐made ASAs by 27 Al MQ MAS NMR experiment. 1 H/ 27 Al TRAPDOR MAS NMR experiments confirmed that surface Al species contribute to the formation of BAS and protonate ammonia probe molecules. The adsorption of ammonia on Lewis acidic Al sites ( δ 1H =3.0 ppm) was evidenced by various 1 H MAS NMR experiments on samples dehydrated at different temperatures, allowing the distinction from ammonium ions ( δ 1H =6.7 ppm) formed at BAS. The signal of ammonia adsorbed on LAS increased with increasing Al content in the ASAs. These properties together with the absence of pore diffusional constraints render the flame‐made ASAs excellent catalysts for cyclohexanol dehydration and the conversion of glyceraldehyde in ethanol to ethyl lactate, outperforming the performance of other ASAs or zeolites. Abstract : Forged in fire : The Flame‐made amorphous silica‐aluminas (ASAs) exhibited excellent catalytic performance for the dehydration of cyclohexane and the conversion of glyceraldehyde to ethyl lactate. The enhanced Brønsted acidity promotes the cyclohexane dehydration providing TOFs up to 7 times higher than those obtained with their co‐condensed counterparts and 20 times higher reaction rates based on unit surface area (mol m −2  s −1 ) than those prepared by ALD and CLD.